Kesantunan Berbahasa Siswa dalam Berdiskusi - Fitria Cahyaningrum; NFN Andayani; Budhi Setiawan (Madah: Jurnal Bahasa dan Sastra, 2018)
Discussion activities can be an effort in improving students' speaking skills through the disclosure of ideas and opinions about a problem. However, sometimes the use of language that is less polite when students express their opinions still appears. There is a need for polite discussion with proper diction when interacting with others. This study aims to describe the form of students' language politeness in class discussions and the characteristics of lingual marker. The method used is descriptive qualitative research with sociopragmatic approach. Data are in the form of students' speech in discussion. Technique of collecting data is by recording technique with free listening method (SBLC). Data analysis techniques use interactive model in the form of data collection, data reduction, data analysis, and conclusion. The results show that there are tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim.  The characteristic markers of linguistic politeness are “silakan”, “tolong”, “maaf”, “terima kasih”, and “mari”.